Light fragment yields from central Au+Au collisions at 11.5 A GeV/c - Barrette, Jean; Stachel, Johanna; Wessels, Johannes P. (Arxiv, 2000)
Inclusive double differential multiplicities of deuterons, ^3H, ^3He, and ^4He measured by E877 for 11.5 A GeV/c Au+Au collisions at the AGS are presented. Light fragments at beam-rapidity are measured for the first time at AGS energies. Beam rapidity deuteron and ^4He yields and transverse slope parameters are found to be strongly dependent on impact parameter and the shape of the deuteron spectra is not consistent with that expected for a simple thermal distribution. The deuteron yields relative to proton yields are analyzed in terms of a simple coalescence model. While results indicate an increase in source size compared to collisions of lighter systems at the same energy, they are inconsistent with a simple coalescence model reflected by a rapidity dependence of the coalescence parameter B_d. A new approach utilizing an expanding thermalized source combined with a coalescence code is developed for studying deuteronformation in heavy-ion collisions. The strong dependence of deuteron yields on collective motion implies that deuteron yields relative to those of protons can be used for constraining source parameters.